2007
DOI: 10.1103/physrevlett.98.217602
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed Dependence of Polarization on Epitaxial Strain in Highly Polar Ferroelectrics

Abstract: A combined experimental and computational investigation of coupling between polarization and epitaxial strain in highly polar ferroelectric PbZr 0.2 Ti 0.8 O 3 (PZT) thin films is reported. A comparison of the properties of relaxed (tetragonality c/a ≈ 1.05) and highly-strained (c/a ≈ 1.09) epitaxial films shows that polarization, while being amongst the highest reported for PZT or PbTiO 3 in either film or bulk forms (P r ≈ 82 μC/cm 2 ), is almost independent of the epitaxial strain. We attribute this behavio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
84
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 156 publications
(93 citation statements)
references
References 34 publications
7
84
0
2
Order By: Relevance
“…Nevertheless, they are easy to process with standard DFT techniques and can still provide useful information on the basic geometrical parameters of the substituted system. 26 Figure 1(a) shows 2θ − ω scans of Sn-alloyed SrTiO 3 films on SrTiO 3 (001) substrates grown at a fixed Ti BEP (1.27 × 10 6 Torr) and at different Sn BEPs (1.63 × 10 7 -3.5 × 10 6 Torr). No secondary phases were observed.…”
Section: © 2016 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…Nevertheless, they are easy to process with standard DFT techniques and can still provide useful information on the basic geometrical parameters of the substituted system. 26 Figure 1(a) shows 2θ − ω scans of Sn-alloyed SrTiO 3 films on SrTiO 3 (001) substrates grown at a fixed Ti BEP (1.27 × 10 6 Torr) and at different Sn BEPs (1.63 × 10 7 -3.5 × 10 6 Torr). No secondary phases were observed.…”
Section: © 2016 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…1,2,13,14 However, if additional parameters ͑composition, microstructure, thickness͒ vary among these films, it is impossible to measure the true effect of strain on properties that are highly sensitive to these parameters, such as coercive fields. Thermal expansion differences between substrate and film can yield well-defined but fixed strain states, 8 whereas bending techniques 15,16 provide reversible strain for films on large substrates ͑wafers͒.…”
mentioning
confidence: 99%
“…Thus, strain effects can now be explored quantitatively in fundamentally and technologically important oxides, [2][3][4][5][6][7][8][9][10] i.e., ferroelectrics, magnetic and optically active oxides, multiferroics, and superconductors. Ab initio theories are increasingly successful in predicting the large strain effect on ferroelectric polarization 2,8,11 and straininduced ferroelectric phases, 1,12 and domain configurations can be controlled by epitaxial strain. 8,10 In two-phase multiferroics, the magnetization of a magnetic component responds to the strain induced by a piezoelectric component, producing a robust magnetoelectric effect.…”
mentioning
confidence: 99%
“…Published reports show that compressive strains (in the plane of the film-substrate interface) may enhance the tetragonal out-of-plane polarization [6,7], while tensile strains induce in-plane rotational phases of the polarization [3]. It was also shown that the impact of in-plane compressive stresses is significantly more pronounced when the variations in the Curie transition temperature are compared to the polarization [8].…”
Section: Introductionmentioning
confidence: 91%